OVERCOMING SEED DORMANCY OF JUNGLERICE (Echinochloa colona) - Picapietra, Gabriel; Acciaresi, Horacio Abel (Chilean Journal of Agricultural & Animal Sciences, 2022)
Junglerice (Echinochloa colona L. Link) seed dormancy can persist 8 months after harvest and, once overcome, seeds can germinate over a long period of time. Light or high temperatures could overcome seed dormancy, while the effects of seed coat softening and nitrate addition are not well known. This study aimed to determine the germinative response, persistence and treatments to overcome seed dormancy of junglerice. Seed samples were taken from a monoculture crop (soybean, S1) and a 3-yr rotation crop (wheat/soybean-corn-soybean, S2). Every 3 wk for 30 wk, hot-water washed (WW) seeds were evaluated. After 33 wk of storage, the effects of potassium nitrate (KNO3), dehulling (DE), WW, previous water immersion (IM) and exogenous gibberellic acid (GA) were evaluated in three different experiments (pre-germinative tests with KNO3, DE and WW; KNO3 and IM; and GA). The results showed that seed dormancy persisted until 21 wk. From 21 to 30 wk, germination response increased by 25 and 59 % on WW-treated seeds from S1 and S2, respectively. After 33 wk of storage, only KNO3 was significantly higher (p < 0.05), with 88 and 126 % increases in seed germination in S1 and S2, respectively. These results indicate that junglerice seed dormancy is not related to glumes. Hot water improves the germinative response probably due to an acceleration in post-harvest maturation, while KNO3 is a positive regulator to overcome seed dormancy.